COMPARACION DE FAUNA DE MICROARTROPODOS ENTRE BOSQUE NATIVO Y PLANTACIONES DE PINUS RADIATA DE REEMPLAZO, EN BIOTOPOS EQUIVALENTES - Covarrubias, Rene (Acta Entomológica Chilena, 2022)
A companson of the microarthropod fauna was made between a native températe forest and a replacement plantation of Pinus radiata in equivalent places. A stratified sampling was made considering two soil horizons. Results are reported for the supraspecific level. Significant differences were found for most taxa, either for the sampling frequencies or the abundances. Abundances were higher in Pinus soils for the most frequent taxa (over 80%); also soil horizon preferences are shown for many of the 36 taxa found in native forest or the 31 found under Pinus All the differences found are interpreted as a new biocenotic order in the Pinus plantation, corresponding to other humification types and soil structure, than in the original native forest.